World City Development In China: A Multifaceted Appraisal Of Chinese Cities In The Era Of Globalization - Li, Zeyun (2019)
A rapid expansion of globalization and diffusion of information has occurred since the beginning of the 21st century. The Chinese economy is a major stimulus that affects the hierarchical structure and system of the world cities network. Three objectives are identified in this research: 1) To examine the overall relationship between the underlying driving forces, locational strategies, and world city formation in the case of Shanghai; 2) To explore the national urban hierarchical structure of financial centres and world cities in China; 3) To measure subregional intercity connections of Chinese cities embedded in the world city network. Social Network Analysis (SNA) has a multifaceted approach to exploring the general status of world city development including Partial Least Square Structural Equation Modelling (PLS-SEM), multiple regression analysis, content analysis, SPSS and factor analysis, the interlocking city network model, and UCINET. This case study of Shanghai uses network analysis of the national urban hierarchy world city network of Chinese cities. This research discusses world city development in China based on the world city hypothesis, the concept of the international division of labour, advance producer services, location theory, agglomeration economy, and, most notably, the theory of the world city network. The three findings of this study evidence a new blueprint of world city formation of Chinese cities in the era of globalization. In relation to case studies pertaining to a preeminent world city in China, that is, Shanghai, two parameters were found to affect world city formation.